To move without moving: a perspective article on motor imagery - Duarte-Mendes, Pedro; Ramalho, André; Bertollo, Maurizio; Neiva, Henrique Pereira; Marinho, Daniel Almeida (Frontiers in Psychology, 2025)
Motor imagery – the mental simulation of movement without execution – activates motor networks with near-physical fidelity. Once considered ancillary, it is now central to neuroplasticity, enhancing skill acquisition, accelerating rehabilitation, and sustaining motor function across the lifespan. From stroke recovery to elite performance, motor imagery demonstrates that movement begins in cognition. As neurofeedback, brain–computer interfaces and virtual reality integrate with mental rehearsal, the boundary between thought and action becomes narrower. This perspective argues that motor imagery is not a cognitive accessory but the neurocognitive foundation of movement – a rehearsal mechanism through which the brain reshapes the body. In doing so, it supports the view that action is cognitively prepared before it is expressed.